Embryonic development of the larval eyes of the Sunburst Diving Beetle, Thermonectus marmoratus (Insecta: Dytiscidae): a morphological study. Issue 4 (July 2016) - Stecher, Nadine; Stowasser, Annette; Stahl, Aaron; Buschbeck, Elke K.
SUMMARY: Stemmata, the larval eyes of holometabolous insects are extremely diverse, ranging from full compound eyes, to a few ommatidial units as are typical in compound eyes, to sophisticated and functionally specialized image‐forming camera‐type eyes. Stemmata evolved from a compound eye ommatidial ancestor, an eye type that is morphologically well conserved in regards to cellular composition, and well studied in regards to development. However, despite this evolutionary origin it remains largely unknown how stemmata develop. In addition, it is completely unclear how development is altered to give rise to some of the functionally most complex stemmata, such as those of the sunburst diving beetle, Thermonectus marmoratus . In this study, we used histological methods to investigate the embryonic development of the functionally complex principal stemmata Eye 1 and Eye 2 of the larval visual system of T. marmoratus . To gain insights into how cellular components of their sophisticated camera‐type eyes might have evolved from the cellular components of ommatidial ancestors, we contrast our findings against known features of ommatidia development, which are particularly well understood in Drosophila . We find many similarities, such as the early presence of a pseudostratified epithelium, and the order in which specific cell types are recruited. However, in Thermonectus each cell type is represented by a large number of cells from early on and major tissue re‐orientation occurs as eye development progresses. This study provides insights into the timing of morphological features and represents the basis for future molecular studies.